Topical silver sulphadiazine–a new drug for ocular keratomycosis. Issue 3 (March 1988) - Mohan, M; Gupta, S K; Kalra, V K; Vajpayee, R B; Sachdev, M S
Abstract : The efficacy of silver sulphadiazine in human keratomycosis has not been evaluated so far. Encouraged by the success of an earlier experimental trial, a prospective, controlled, randomised double masked clinical study was designed to evaluate the efficacy of 1% silver sulphadiazine ophthalmic ointment in 20 eyes of mycotic keratitis. Miconazole 1% was used for comparative evaluation in another 20 eyes. Silver sulphadiazine had a higher success rate (80% vs 55%) than miconazole. It had broad antifungal activity and was found to be effective in fusarium keratitis. Absence of side effects, economy, and its efficacy in deeper and extensive lesions were additional advantages. It is concluded from this study that silver sulphadiazine is a safe and effective broad spectrum antifungal agent which can be used for the treatment of human keratomycosis.